CODE-SWITCHING IN SUNNYDAHYE’S INSTAGRAM CAPTIONS - Clara Clara; Annisa Agra Inggitajna (UC Journal: ELT, Linguistics and Literature Journal, 2021)
Instagram has become one of the most used social-networking websites. In the use of communication, Instagram also provides the user to communicate through picture and video with an addition of caption to explain the media in words. To express oneself on Instagram, some users might use the combination of their first language and English. Thus the phenomena of code-switching occurs. This paper aims to analyse the type and function of code-switching used in one Instagram account, sunnydahye. This paper uses a qualitative approach to provide insights to the problems. The data for this paper is selected by using a purposive sampling method by checking sunnydahye’s Instagram post one by one. From 6 instagram posts taken as the sample, there are 22 sentences identified with a phenomena of code switching. The result of the analysis shows that the type of code-switching which is used most in sunnydahye’s Instagram caption is intra-sentential switching. Meanwhile the function of code-switching which is used most is code-switching as message qualification.